AgNP-coordinated glucosamine-grafted carbon nanotubes with enhanced antibacterial properties. (26th June 2017) - Hao, X. P.; Chen, S. G.; Wang, W. H.; Yang, Z. Q.; Yue, L. F.; Sun, H. Y.; Cheng, F.
Abstract : After glucosamine is coated on MWCNTs, the bonding force between the AgNPs and MWCNT–glucosamine increases because the charge of the O atom changes. Abstract : An MWCNT–glucosamine–AgNP composite with long-term antibacterial properties, good dispersity, and stability in aqueous solutions was synthesized by a grafting method. Various surface analysis techniques were used to determine the successful preparation of MWCNT–glucosamine–AgNPs. The release behavior of Ag was detected by ICP-Q, and the long-term antibacterial effect against Staphylococcus aureus was characterized by the counting method. It was found that, after modification of the MWCNTs with glucosamine, the interfacial adsorption of Ag was significantly enhanced. The concentration of Ag ions released in the PBS solution was only 0.0643 ppm after 35 days of immersion. The MWCNT–glucosamine–AgNPs maintained effective antibacterial properties, and the bacteriostatic percentage of S. aureus was maintained at 90% after 35 days. This study demonstrated the great potential of MWCNT–glucosamine–AgNPs as a long-term antibacterial agent for use in the public health and antibacterial coating fields.